Tantangan Dan Peluang Digital Marketing Bagi UMKM Berbasis E-Commerce di Kepulauan Nias - Nov Elhan Gea (Jurnal Ilmu Sosial Dan Politik, 2025)
The development of digital marketing and e-commerce has created new opportunities for Micro, Small, and Medium Enterprises (MSMEs) to expand market reach and enhance competitiveness. However, the adoption of digital marketing by MSMEs in island regions still faces various challenges, particularly related to geographical conditions, digital infrastructure, and human resource capacity. This study aims to analyze the level of digital marketing adoption based on e-commerce, identify the challenges faced, and examine potential opportunities for digital marketing development among MSMEs in the Nias Islands, covering Gunungsitoli City, South Nias Regency, West Nias Regency, Nias Regency, and North Nias Regency. This research employs a qualitative descriptive approach using secondary data collected through literature review and document analysis, including publications from Statistics Indonesia, government reports, and relevant previous studies. The findings indicate that the main challenges of digital marketing adoption among MSMEs in the Nias Islands include technical and internet infrastructure constraints, limited digital literacy and human resource capabilities, as well as capital and technology limitations, with varying levels of dominance across regions. On the other hand, significant opportunities were identified, such as the growing digital market potential, the utilization of social media and e-commerce marketplaces as primary marketing channels, and the support of the digital ecosystem provided by government initiatives and digital platforms. This study concludes that the development of e-commerce-based MSMEs in the Nias Islands largely depends on the ability to reduce digital marketing challenges while optimizing available opportunities in a contextual and sustainable manner. The results are expected to serve as a basis for formulating digital marketing strategies and MSME empowerment policies that are aligned with the characteristics of island regions.